Penerapan Pendekatan Contextual Teaching and Learning dalam Pembelajaran PAI dan Implikasinya terhadap Kemampuan Berpikir Kritis Siswa: The Application of Contextual Teaching and Learning Approach in Islamic Religious Education (PAI) and Its Implications on Students' Critical Thinking Skills - Mu'min, Wandi Syahrul; Rohayani, Ai; Ginanjar, Wahyu (Epistemic: Jurnal Ilmiah Pendidikan, 2025)
This research examines the implementation of the Contextual Teaching and Learning (CTL) approach in Islamic Religious Education at SMAN 1 Sindangbarang and its implications for the development of students' critical thinking skills. A qualitative study with a descriptive approach was conducted, involving the School Principal, Islamic Religious Education teachers, and students as research subjects. The findings indicate that CTL effectively enhances the efficiency of teaching and learning activities and improves students' critical thinking abilities. However, certain aspects need improvement. It is essential to clearly outline the research limitations to help readers understand the context and generalize the findings. The data analysis should be elaborated in more detail to enhance the validity of the results. Additionally, the challenges identified should be specified more clearly, and proposed solutions need to be presented comprehensively. The effectiveness of learning measurement using the CTL concept should be supported by more concrete and measurable data. Furthermore, the findings should be linked to the national curriculum and educational standards to strengthen the relevance of the results. The implications for enhancing teacher professionalism should be detailed, encompassing specific steps taken by the school. Practical recommendations to address challenges and strengthen the implementation of CTL need to be clearly outlined, with encouragement to explore the impact of CTL implementation in a broader context.